Respuesta :
Answer:
y=-1
Step-by-step explanation:
The first step to solving this problem is to write it out like this-->
4x+2y=6
x-3y=5
Next you want to eliminate the X's or the Y's, I chose to elininate the X's-->
4x+2y=6
-4(x-3y=5) [You MUST distribute the -4 to each of the numbers in the equation]
Then you get--->
4x+2y=6
-4x+12y=-20 Then you add them top to bottom--->
0x+14y=-14 [At this point you dont have to write the X]Next you solve for y-->
14y=-14 Divide both sides by 14, in order to get the y by itself-->
y=-1 And theres your answer hope it helps :D
we have the 2 equations
4x + 2y = 6 → (1)
x - 3y = 5 → (2)
multiply (2) by 4
4x - 12y = 20 → (3)
(3) - (1) to eliminate the terms in x
- 14y = 14 ( divide both sides by - 14 )
y = - 1
substitute y = - 1 into (1) and solve for x
4x - 2 = 6 ) add 2 to both sides )
4x = 8 ( divide both sides by 4 )
x = 2
solution is x = 2, y = - 1